Chemical Composition and Quorum Sensing Inhibitory Effect of Nepeta curviflora Methanolic Extract against ESBL Pseudomonas aeruginosa - Haitham Qaralleh (Korean Pharmacopuncture Institute, 2023)
Objectives: Bacterial biofilm is regarded as a significant threat to the production of safe food and the arise of antibiotic-resistant bacteria. The objective of this investigation is to evaluate the quorum sensing inhibitory effect of Nepeta curviflora methanolic extract. Methods: The effectiveness of the leaves at sub-inhibitory concentrations of 2.5, 1.25, and 0.6 mg/mL on the virulence factors and biofilm formation of P. aeruginosa was evaluated. The effect of N. curviflora methanolic extract on the virulence factors of P. aeruginosa, including pyocyanin, rhamnolipid, protease, and chitinase, was evaluated. Other tests including the crystal violet assay, scanning electron microscopy (SEM), swarming motility, aggregation ability, hydrophobicity and exopolysaccharide production were conducted to assess the effect of the extract on the formation of biofilm. Insight into the mode of antiquorum sensing action was evaluated by examining the effect of the extract on the activity of N-Acyl homoserine lactone (AHL) and the expression of pslA and pelA genes. Results: The results showed a significant attenuation in the production of pyocyanin and rhamnolipid and in the activities of protease and chitinase enzymes at 2.5 and 1.25 mg/mL. In addition, N. curviflora methanolic extract significantly inhibited the formation of P. aeruginosa biofilm by decreasing aggregation, hydrophobicity, and swarming motility as well as the production of exopolysaccharide (EPS). A significant reduction in AHL secretion and pslA gene expression was observed, indicating that the extract inhibited quorum sensing by disrupting the quorum-sensing systems. The quorum-sensing inhibitory effect of N. curviflora extract appears to be attributed to the presence of kaempferol, quercetin, salicylic acid, rutin, and rosmarinic acid, as indicated by LCMS analysis. Conclusion: The results of the present study provide insight into the potential of developing anti-quorum sensing agents using the extract and the identified compounds to treat infections resulting from quorum sensing-mediated bacterial pathogenesis.